2016
DOI: 10.1186/s12885-016-2779-y
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of γ-glutamylcyclotransferase inhibits breast cancer cell growth via cellular senescence induction mediated by CDK inhibitor upregulation

Abstract: BackgroundChromosome 7 open reading frame 24 (C7orf24) was originally identified as a highly expressed protein in various types of cancer, and later shown to be a γ-glutamylcyclotransferase (GGCT). GGCT depletion in cancer cells has anti-proliferative effects in vitro and in vivo, and it is therefore considered a promising candidate as a therapeutic target. However, the cellular events induced by GGCT depletion remain unclear.MethodsGGCT was depleted by siRNA in MCF7, MDA-MB-231, PC3, A172, Hela, and LNCaP cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…NF-Y and Sp1 bind to the CCAAT boxes and to the GC box, respectively, to positively regulate transcription of the GGCT gene. Since promoters with several NF-Y-binding CCAAT boxes were found in genes related to the cell cycle, Ohno et al suggested that GGCT may also play a role in the cell cycle [ 18 ], as confirmed by other studies [ 19 , 20 , 21 , 22 ].…”
Section: Molecular Regulation Mechanism Of Ggct Expression In Cancmentioning
confidence: 85%
See 2 more Smart Citations
“…NF-Y and Sp1 bind to the CCAAT boxes and to the GC box, respectively, to positively regulate transcription of the GGCT gene. Since promoters with several NF-Y-binding CCAAT boxes were found in genes related to the cell cycle, Ohno et al suggested that GGCT may also play a role in the cell cycle [ 18 ], as confirmed by other studies [ 19 , 20 , 21 , 22 ].…”
Section: Molecular Regulation Mechanism Of Ggct Expression In Cancmentioning
confidence: 85%
“…Dong et al also reported that GGCT knockdown blocked cell cycle progression at the G0/G1 phase in both HCT116 and in SW1116 colorectal cancer cells [ 21 ]. Matsumura et al observed G0/G1 arrest in MCF7 breast cancer cells [ 22 ]. In contrast, Zhang et al analyzed cell cycle change using a gastric cancer cell line, MGC80-3, and reported a significant reduction of cell cycle progression in shGGCT cells, with a reduction of the cell population in the G0/G1 phase and a corresponding increase in the G2/M phase when compared with the control cells [ 20 ].…”
Section: Inhibition Of Cancer Cell Proliferation and Induction Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that the downregulation of GGCT elicits an anti-proliferative effect in some cancer cell lines, such as breast cancer cell lines MCF-7, MCF-7/ADR, and MDA-MB-231 [44][45][46]. Interestingly, ChaC1 was suggested as a novel biomarker because the overexpression of mammalian ChaC1 and its related transcript variants has been previously found to promote cell proliferation in breast cancer cell lines Hs578T and BT-20 [18,47,48].…”
Section: Chac2 Overexpression Promotes Cell Proliferation In the Mcf-mentioning
confidence: 99%
“…Senescence is a critical and irreversible cellular program characterized by changes in the behavior, function, and morphology of cells and tissues [27]. Various stimuli, such as oncogene activation, DNA lesion, cytotoxic stimulation, and inflammatory stress, can lead to senescence.…”
Section: Discussionmentioning
confidence: 99%